Role of interleukin-4 receptor α polymorphism in patients with asthma and its correlation with asthma severity - Nidhi Girdhar; Karan Sharma; Satyajit Deshpande; Siddharth Sharma; Vishal Chopra; Anil Sontakke (Monaldi Archives for Chest Disease)
Asthma is a heterogeneous disease characterized by chronic airway inflammation. It is defined by the history of respiratory symptoms such as wheeze, shortness of breath, chest tightness, and cough that vary over time and intensity, together with variable expiratory airflow limitation. A personal history or a family history of allergy is the factor most strongly associated with the development of asthma. Our primary aim was to investigate interleukin-4 receptor α (IL-4Rα) polymorphism to determine whether the presence of the R576 IL-4Rα allele was associated with asthma and whether the presence of the R576 allele influenced the severity of asthma in affected individuals. The data obtained indicated asthmatic patients were characterized by a higher prevalence of positive family history of asthma (p<0.001) as compared to controls. It was found that the patients homozygous for mutant alleles had a 1.39-fold increased risk of asthma compared with individuals not homozygous for R576. Also, we found that females had higher odds (1.61-fold) of significant association with asthma (p=0.09; odds ratio=1.58). While this report clearly necessitates a more detailed study, it is plausible that IL-4 mutation has a significant role in the development of asthma and, thus, can play an important role in developing targeted therapy.